Effect of test setup on the fiber-to-mortar pull-out response in TRM composites: experimental and analytical modeling - Dalalbashi, Ali; Ghiassi, Bahman; Oliveira, Daniel V.; Freitas, Ana (Elsevier, 2018)
Textile-reinforced mortars (TRM) have recently received significant attention for the externally bonded reinforcement (EBR) of masonry and reinforced concrete structures. The fiber-to-mortar bond, the TRM-to-substrate bond, and the mechanical properties of the TRM constituents have a fundamental role in the performance of this strengthening technique and therefore require special attention. Despite this importance, only few investigations are devoted to characterization of the single fiber-to-mortar bond response in these systems. This paper, as an step towards addressing the fiber-to-mortar bond, presents a combined experimental and analytical investigation on the effect of test setup on the pull-out response and bond-slip laws in TRM composites. Three different pull-out test setups, consisting of one pull-pull and two pull-push configurations, are developed and investigated for characterization of the single fiber-to-mortar bond behavior. The experimental and analytical results are critically discussed and presented and bond-slip laws are extracted for each test setup.